2011
DOI: 10.1007/s12011-011-9207-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Calcium on Non-heme Iron Uptake, Efflux, and Transport in Intestinal-like Epithelial Cells (Caco-2 Cells)

Abstract: It has been suggested that calcium inhibits the absorption of dietary iron by directly affecting enterocytes. However, it is not clear if this effect is due to a decreased uptake of iron or its efflux from enterocytes. We studied the effect of calcium on the uptake, efflux, and net absorption of non-heme iron using the intestinal-like epithelial cell line Caco-2 as an in vitro model. Caco-2 cells were incubated for 60 min in a buffer supplemented with non-heme iron (as sulfate) and calcium to achieve calcium t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…To ensure that the monolayers were intact with fully-formed tight junctions, trans -epithelial electrical resistance (TEER) and phenol red flux were routinely assessed, as we described previously 15, 16 . For IEC-6 cells, TEER values were routinely 36 – 40 Ω/cm 2 and >250 Ω/cm 2 for Caco-2 cells.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that the monolayers were intact with fully-formed tight junctions, trans -epithelial electrical resistance (TEER) and phenol red flux were routinely assessed, as we described previously 15, 16 . For IEC-6 cells, TEER values were routinely 36 – 40 Ω/cm 2 and >250 Ω/cm 2 for Caco-2 cells.…”
Section: Methodsmentioning
confidence: 99%
“…In agreement with these results, a previous study performed by us, and recently published by Gaitan et al [15] found that doses ≤800 mg of Ca (CaCl 2 ) did not decrease the bioavailability of 5 mg of Fe (FeSO 4 ) in subjects with similar characteristics. Also, a study focused on the effect of calcium on uptake, efflux, and net absorption of non-heme iron using the intestinal-like epithelial Caco-2 cell found that calcium did not have an effect on the net absorption of non-heme iron [39].…”
Section: Subjectmentioning
confidence: 99%
“…The author reported that there were no signifi cant differences in the DMT1 mRNA expression between the cells incubated in the absence or presence of calcium for 1.5 h (p=0.06). However, the cells cultured for 4 hours with 100μM calcium demonstrated a signifi cant increase in DMT1 expression (p-value not reported), which may explain the fi ndings obtained by Gaitan et al (37), who observed that calcium signifi cantly increases iron uptake in Caco-2 cells. Regarding Fpn mRNA expression, Lönnerdal (36) found no signifi cant differences between the cells incubated with and without calcium for 1.5 or 4 hours.…”
Section: Studies On Calcium and Its Effect On Iron Absorption In A Cementioning
confidence: 86%
“…Conversely, in a review on this subject, Lönnerdal (36) reported that there is a decrease in basolateral iron transport in Caco-2 cells incubated in the presence of 1 μM Fe (FeSO4) and 100 μM calcium chloride compared with cells cultured in the absence of calcium; the culture times were 1.5 and 4 hours (the Ca:Fe molar ratios were 0:1 and 100:1, respectively). Moreover, Gaitan et al (37) evaluated, the effect of calcium (in the form of calcium chloride) on the uptake, effl ux, and net absorption of a 2 μM iron solution (FeSO4) in Caco-2 cells; the calcium was administered at Ca:Fe molar ratios of 50:1 -1000:1. In this study, calcium did not affect the net absorption of iron; however, iron uptake by the cells was signifi cantly higher than uptake by the control group at molar ratios of 500:1 and 1000:1(ANOVA p<0.009), while the effl ux of iron decreased signifi cantly at a molar ratio of 1000:1 (ANOVA p<0.002).…”
Section: Studies On Calcium and Its Effect On Iron Absorption In A Cementioning
confidence: 99%